Growth differentiation factor-15 is a predictive biomarker in primary ventricular fibrillation: The RUTI-STEMI-PVF study. Issue 4 (November 2020) - Garcia-Garcia, C; Rueda, F; Lupon, J; Oliveras, T; Labata, C; Ferrer, M; Cediel, G; De Diego, O; Rodriguez-Leor, O; Carrillo, X; Bayes-Genis, A
Background: Primary ventricular fibrillation is an ominous complication of ST-segment elevation myocardial infarction, and proper biomarkers for risk prediction are lacking. Growth differentiation factor-15 is a marker of inflammation, oxidative stress and hypoxia with well-established prognostic value in ST-segment elevation myocardial infarction patients. We explored the predictive value of growth differentiation factor-15 in a subgroup of ST-segment elevation myocardial infarction patients with primary ventricular fibrillation. Methods: Prospective registry of ST-segment elevation myocardial infarction patients treated with primary percutaneous coronary intervention from February 2011–August 2015. Growth differentiation factor-15 concentrations were measured on admission. Logistic regression and Cox proportional regression analyses were used. Results: A total of 1165 ST-segment elevation myocardial infarction patients treated with primary percutaneous coronary intervention (men 78.5%, age 62.3±13.1 years) and 72 patients with primary ventricular fibrillation (6.2%) were included. Compared to patients without primary ventricular fibrillation, median growth differentiation factor-15 concentration was two-fold higher in ST-segment elevation myocardial infarction patients with primary ventricular fibrillation (2655 vs 1367 pg/ml, p <0.001). At 30 days, mortality was 13.9% and 3.6% in patients with and without primary ventricular fibrillation, respectively ( p <0.001), and median growth differentiation factor-15 concentration in patients with primary ventricular fibrillation was five-fold higher among those who died vs survivors (13, 098 vs 2415 pg/ml, p <0.001). In a comprehensive multivariable analysis including age, sex, clinical variables, reperfusion time, left ventricular ejection fraction, N-terminal pro-B-type natriuretic peptide and high-sensitivity troponin T, growth differentiation factor-15 remained an independent predictor of 30-day mortality, with odds ratios of 3.92 (95% confidence interval 1.35–11.39) in patients with primary ventricular fibrillation ( p =0.012) and 1.72 (95% confidence interval 1.23–2.40) in patients without primary ventricular fibrillation ( p =0.001). Conclusions: Growth differentiation factor-15 is a robust independent predictor of 30-day mortality in ST-segment elevation myocardial infarction patients with primary ventricular fibrillation.